Remote operation and monitoring of a micro aero gas turbine. (21st June 2017) - Diakostefanis, M.; Nikolaidis, T.; Sampath, S.; Triantafyllou, T.
ABSTRACT: Internet applications have been extended to various aspects of everyday life and offer services of high reliability and security at relatively low cost. This project presents the design of a reliable, safe and secure software system for real-time remote operation and monitoring of an aero gas turbine with utilisation of existing internet technology, whilst the gas turbine is installed in a remote test facility This project introduces a capability that allows remote and flexible operation of an aero gas turbine throughout the whole operational envelope, as required by the user at low cost, by exploiting the available Internet technology. Remote operation of the gas turbine can be combined with other remote Internet applications to provide very powerful gas-turbine performance-simulation experimental platforms and real-time performance monitoring tools, whilst keeping the implementation cost at low levels. The gas turbine used in this experiment is an AMT Netherlands Olympus micro gas turbine and a spiral model approach was applied for the software. The whole process was driven by risk mitigation. The outcome is a fully functional software application that enables remote operation of the micro gas turbine whilst constantly monitors the performance of the engine according to basic gas turbine control theory. The application is very flexible, as it runs with no local installation requirements and includes provisions for expansion and collaboration with other online performance simulation and diagnostic tools.